The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/s18030884
|View full text |Cite
|
Sign up to set email alerts
|

Unannounced Meals in the Artificial Pancreas: Detection Using Continuous Glucose Monitoring

Abstract: The artificial pancreas (AP) system is designed to regulate blood glucose in subjects with type 1 diabetes using a continuous glucose monitor informed controller that adjusts insulin infusion via an insulin pump. However, current AP developments are mainly hybrid closed-loop systems that include feed-forward actions triggered by the announcement of meals or exercise. The first step to fully closing the loop in the AP requires removing meal announcement, which is currently the most effective way to alleviate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Regarding the meals, even though MPC-based AP is naturally robust to bad announced meals, studies have revealed that its performance is significantly degraded when the size of meals increases [37]. To deal with this condition, two augmented doubleintegrator observers are proposed to have an offset-free behavior under both, partially-announced and unannounced meals scenarios, as well as to cope with moderate plant-model uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the meals, even though MPC-based AP is naturally robust to bad announced meals, studies have revealed that its performance is significantly degraded when the size of meals increases [37]. To deal with this condition, two augmented doubleintegrator observers are proposed to have an offset-free behavior under both, partially-announced and unannounced meals scenarios, as well as to cope with moderate plant-model uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Current artificial pancreas systems also have several challenges that need to be addressed if they are to be used in conjunction with bioelectronic medicine. Among them, the delays in interstitial glucose sensing and hormonal subcutaneous absorption (Ramli et al 2019;Taleb et al 2019;Gingras et al 2018;Herrero et al 2017), failures in the insulin pump (Meneghetti et al 2018), and glycaemic control during meals (Ramkissoon et al 2018) and exercise (Ramkissoon et al 2020) are the most critical. Despite these challenges, the use of the artificial pancreas is associated with high levels of satisfaction and quality of life, and reduced fear of hypoglycaemic events among the users (Ramli et al 2019).…”
Section: Challengesmentioning
confidence: 99%
“…Where a truly closed-loop system could deliver insulin autonomously, the hybrid system still works best when the user alerts the insulin pump before eating and gives themselves a dose of insulin to cover the food that will be consumed (FDA, 2018b). Although, research has shown that the system is capable of adjusting the prandial dose to cover a meal, currently available short-acting insulin does not act rapidly enough to maintain the appropriate blood glucose level after a meal (Ramkissoon, Herrero, Bondia, & Vehi, 2018).…”
Section: How Does the System Work?mentioning
confidence: 99%